A Comparative Study on Financial Performance of the Participants in Indonesia Sustainability Reporting Awards - Hatane Semuel; Saarce Elsye Hatane; Cyndy Fransisca; Josua Tarigan; Jean-Marc Dautrey (Universitas Pasundan, 2019)
The main objective of this research is to analyze the financial performance of companies that have participated in Indonesia Sustainability Reporting Awards (ISRA) competitions in 2009–2017, both regularly and temporarily. This study also analyzes the differences in financial performance in terms of industrial sector factors and the number of workers. This research applies secondary data, which is carried out with independent t–test and multivariate test. Companies that consistently participate in ISRA competitions have a smaller level of leverage, and more exceptional ability to generate operating cash. Companies with fewer than two thousand employees are more productive than companies with ten thousand employees. However, when the number of employees is more than ten thousand people, productivity managing assets is even better. It seems that investors appreciate small companies more. Compared to companies in the banking sector, companies in the manufacturing and non–manufacturing industries have more substantial debts, more productive assets, and higher stock market values. It seems that investors appreciate this ISRA competition more for non–banking companies.